Penerapan Pembiasaan Kegiatan Keagamaan dalam Membentuk Karakter Disiplin Siswa di SMPN 17 Pekanbaru - Aisy Funny, Radiatul; Sukmawati; Syafi'i, Muhammad (Kilau Publishing, 2023)
Instilling character education, especially discipline, is an important thing to instill in students from a young age. The purpose of this study was to determine the objective conditions of the habituation of religious activities, to know the discipline and religious character of students, and to know the influence of the habituation of religious activities on the character of student discipline at SMPN 17 Pekanbaru. This research is a qualitative descriptive study using observation and documentation data collection techniques. The results showed that the habituation of religious activities at SMPN 17 Pekanbaru had a significant effect on student discipline.